Lithium iron phosphate positive electrode material and preparation method thereof, positive electrode plate and secondary battery

By preparing lithium iron phosphate positive electrode material with a surface mesoporous structure, the problem of poor strain ability of the material is solved, and its circulation performance and battery service life are significantly improved.

CN119390035APending Publication Date: 2025-02-07SHENZHEN DYNANONIC CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411531687.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The strain capacity of lithium iron phosphate positive electrode material is poor, which is prone to cracks, resulting in poor circulation performance.

Method used

Using a preparation method, a lithium iron phosphate positive electrode material with a surface mesoporous structure is formed by mixing a carbon source and a dry yeast with an iron source and a phosphorus source, and then dried and sintered.

Benefits of technology

It improves the circulation stability of lithium iron phosphate positive electrode material, reduces the deformation and cracks of particles during the circulation process, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390035A_ABST
    Figure CN119390035A_ABST
Patent Text Reader

Abstract

The invention discloses a lithium iron phosphate positive electrode material and a preparation method thereof, a positive electrode plate and a secondary battery, and the preparation method comprises the following steps: adding a carbon source and dry yeast into a solvent, and culturing the dry yeast to obtain a first solution; sequentially mixing the dissolved iron source and the dissolved phosphorus source into the first solution, and drying to obtain a ferrophosphorus intermediate; fully mixing the ferrophosphorus intermediate with a lithium source to obtain a precursor; and sintering the precursor, and crushing to obtain the lithium iron phosphate positive electrode material with the surface mesoporous structure. The lithium iron phosphate positive electrode material has good strain capacity in the cycle process, deformation and cracking of particles in the cycle process are reduced, lithium consumption is reduced, and the lithium iron phosphate positive electrode material has excellent cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium-ion batteries, and in particular to a lithium iron phosphate positive electrode material and a preparation method thereof, a positive electrode sheet and a secondary battery. Background Art

[0002] The cathode material is one of the core materials of lithium batteries. Its performance directly affects the energy density, safety, life and application of lithium batteries, accounting for more than 30% of the total material cost of batteries. At present, the common cathode materials for lithium-ion batteries in the industry can be mainly divided into lithium iron phosphate (LFP), ternary materials (NCM, NCA), lithium manganese oxide (LMO), lithium cobalt oxide (LCO), etc. The binding force of the phosphate chemical bond of lithium iron phosphate is stronger than that of the traditional transition metal oxide structure chemical bond, so its structure is more stable and it is not easy to release oxygen. Therefore, the safety performance of lithium iron phosphate cathode materials is much higher than that of ternary materials, lithium cobalt oxide and lithium manganese oxide, and it has become an important research direction in the field of energy storage materials.

[0003] However, the deterioration of lithium iron phosphate cycle performance is mainly due to the continuous stress on the particles during the cycle process, which causes cracks on the particle surface, thereby consuming active lithium to generate new interface films and even new side reactions, accelerating battery degradation. Therefore, how to improve the strain capacity of lithium iron phosphate positive electrode materials and optimize the cycle performance of materials has become the key. Summary of the invention

[0004] The purpose of the present application is to provide a lithium iron phosphate positive electrode material and a preparation method thereof, a positive electrode plate and a secondary battery, so as to solve the problem that the lithium iron phosphate positive electrode material in the prior art has poor strain capacity and is prone to cracking.

[0005] To achieve the purpose of this application, this application provides the following technical solutions:

[0006] In a first aspect, the present application provides a method for preparing a lithium iron phosphate positive electrode material, the preparation method comprising: adding a carbon source and dry yeast into a solvent, and culturing the dry yeast to obtain a first solution; sequentially mixing a dissolved iron source and a dissolved phosphorus source into the first solution, and obtaining a ferrophosphorus intermediate after drying; fully mixing the ferrophosphorus intermediate with a lithium source to obtain a precursor; sintering and crushing the precursor to obtain a lithium iron phosphate positive electrode material having a surface mesoporous structure.

[0007] In one embodiment, the dry yeast is cultured at a temperature ranging from 25° C. to 30° C., and the dry yeast is cultured for a time ranging from 0.1 h to 1.5 h.

[0008] In one embodiment, the dissolved iron source and the dissolved phosphorus source are sequentially mixed into the first solution, and a ferrophosphorus intermediate is obtained after drying, comprising: mixing the dissolved iron source into the first solution, and obtaining a second solution after sufficient stirring; mixing the dissolved phosphorus source into the second solution, and obtaining the ferrophosphorus intermediate after drying.

[0009] In one embodiment, the stirring temperature range of the iron source after being mixed into the first solution is 25° C. to 40° C., and the stirring time range is 3 h to 20 h.

[0010] In one embodiment, the pH value of the solution after the phosphorus source is mixed into the second solution is in the range of 4.5 to 7 during stirring, the stirring time is in the range of 0.5 h to 3 h, and the standing time after stirring is in the range of 5 h to 24 h.

[0011] In one embodiment, the ferrophosphorus intermediate is fully mixed with a lithium source to obtain a precursor, including: fully ball-milling the ferrophosphorus intermediate and the lithium source, and rolling the obtained solid after mixing to obtain the precursor.

[0012] In one embodiment, the ferrophosphorus intermediate is fully mixed with a lithium source to obtain a precursor, including: fully ball-milling the ferrophosphorus intermediate, the lithium source and the doped metal source, and rolling the obtained solid after mixing to obtain the precursor.

[0013] In one embodiment, the precursor is crushed after sintering, including: placing the precursor in an inert atmosphere for a first sintering stage, and crushing the solid obtained after the first sintering stage to obtain a sintered product; placing the sintered product in an inert atmosphere for a second sintering stage, and crushing the solid obtained after the second sintering stage to obtain the lithium iron phosphate positive electrode material with a surface mesoporous structure.

[0014] In one embodiment, the heating rate of the first sintering stage is in the range of 1°C / min to 10°C / min, the sintering temperature of the first sintering stage is in the range of 150°C to 360°C, and the sintering time of the first sintering stage is in the range of 1h to 10h.

[0015] In one embodiment, the heating rate of the second sintering stage is in the range of 12°C / min to 20°C / min, the sintering temperature of the second sintering stage is in the range of 650°C to 750°C, and the sintering time of the second sintering stage is in the range of 5h to 15h.

[0016] In one embodiment, the ratio of the added mass of the dry yeast to the molar amount of the iron element in the iron source is 1 g to 10 g: 1 mol.

[0017] In one embodiment, the added mass of the carbon source is 3% to 10% of the theoretical output of the lithium iron phosphate positive electrode material.

[0018] In one embodiment, the molar ratio of the iron source, the phosphorus source, and the lithium source is in the range of (0.93-0.99): (0.98-1.00): (1.01-1.08).

[0019] In one embodiment, the groups carried by the dry yeast include one or more of carboxyl groups, phosphate groups, and sulfonic acid groups.

[0020] In one embodiment, the carbon source includes one or more of glucose, maltose, fructose, and sucrose.

[0021] In one embodiment, the iron source includes one or more of ferric nitrate, ferrous nitrate, ferric sulfate, ferrous sulfate, ferric chloride, ferrous chloride, ferrous acetate, and ferrous acetate.

[0022] In one embodiment, the phosphorus source includes one or more of phosphoric acid, ammonium hydrogen phosphate, diammonium hydrogen phosphate, sodium phosphate, and potassium phosphate.

[0023] In one embodiment, the lithium source includes one or more of lithium oxide, lithium hydroxide, lithium oxalate, lithium carbonate, lithium acetate, and lithium phosphate.

[0024] In a second aspect, the present application provides a lithium iron phosphate positive electrode material, the surface of which has a mesoporous structure, the pores of the mesoporous structure are evenly distributed and the pore size is between 40nm and 50nm.

[0025] In one embodiment, the lithium ion transmission rate of the lithium iron phosphate positive electrode material is in the range of 1.06×10 - 13 m 2 / s~1.00×10 -14 m 2 / s.

[0026] In one embodiment, the electronic conductivity of the lithium iron phosphate positive electrode material is in the range of 1×10 -7 S / cm~1×10 -8 S / cm.

[0027] In a third aspect, the present application provides a positive electrode plate, comprising a positive electrode collector and a positive electrode film layer located on at least one surface of the positive electrode collector, wherein the positive electrode film layer comprises the lithium iron phosphate positive electrode material obtained by the preparation method described in the first aspect or the lithium iron phosphate positive electrode material described in the second aspect.

[0028] In a fourth aspect, the present application provides a secondary battery, comprising the lithium iron phosphate positive electrode material obtained by the preparation method described in the first aspect or the lithium iron phosphate positive electrode material described in the second aspect.

[0029] The present application can prepare a lithium iron phosphate positive electrode material with a mesoporous structure on the surface through the above-mentioned preparation method. The biological macromolecules with negative groups of yeast itself are used to adsorb the iron ions and ferrous ions in the iron source around the yeast, and then a phosphorus source is added and the pH is controlled to produce a porous intermediate precipitate. By controlling the culture environment of the yeast, the mesopore diameter on the surface of the lithium iron phosphate positive electrode material can be controlled between 40nm and 50nm. The lithium iron phosphate positive electrode material with this structure can increase the contact area of ​​the material, increase the lithium ion diffusion channel, and increase the lithium ion diffusion rate, which is beneficial to improve the lithium ion conductivity; and when the particles are deformed by stress, the mesopores give the particles a position for deformation, which reduces the generation of cracks in the particles, optimizes the cycle stability of the lithium iron phosphate positive electrode material, and increases the service life of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0031] Figure 1 is a flow chart of a lithium iron phosphate positive electrode material and a preparation method thereof according to an embodiment;

[0032] Figure 2 is a flow chart of step S20 of one embodiment;

[0033] Figure 3 is a flow chart of step S40 of one embodiment;

[0034] Figure 4 is a SEM image of the lithium iron phosphate positive electrode material prepared in Example 1;

[0035] Figure 5 This is a SEM image of the lithium iron phosphate positive electrode material prepared in Comparative Example 1. DETAILED DESCRIPTION

[0036] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0037] Unless otherwise defined, all technical and scientific terms used in this application have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used in this application and in the specification are only for the purpose of describing specific embodiments and are not intended to limit this application. The term "and / or" used in this application includes any and all combinations of one or more of the related listed items.

[0038] It should be noted that the "range" disclosed in the present application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of a particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a particular parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present application, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0039] All steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, a method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, a method may also include step (c), which means that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b, etc.

[0040] In conjunction with the accompanying drawings, some embodiments of the present application are described in detail below. In the absence of conflict, the following embodiments and features in the embodiments can be combined with each other.

[0041] The present application aims to solve the problem that the lithium iron phosphate positive electrode material in the prior art has poor strain capacity and is prone to cracking, and provides a lithium iron phosphate positive electrode material with mesopores on the surface and a preparation method thereof. The lithium iron phosphate positive electrode material synthesized by the preparation method has uniformly distributed mesopores on the surface, and the size is between 40nm and 50nm. The lithium iron phosphate positive electrode material has high conductivity and good strain capacity during the cycle process, which reduces deformation and cracking of particles during the cycle process, reduces lithium consumption, and has excellent cycle performance.

[0042] The present application provides a method for preparing a lithium iron phosphate positive electrode material.

[0043] In one implementation, please refer to Figure 1 The preparation method of lithium iron phosphate positive electrode material comprises the following steps:

[0044] Step S10, adding a carbon source and dry yeast into a solvent, and culturing the dry yeast to obtain a first solution.

[0045] Step S20, mixing the dissolved iron source and the dissolved phosphorus source into the first solution in sequence, and obtaining a ferrophosphorus intermediate after drying.

[0046] Step S30, fully mixing the ferrophosphorus intermediate and the lithium source to obtain a precursor.

[0047] Step S40, sintering the precursor and then crushing it to obtain a lithium iron phosphate positive electrode material with a surface mesoporous structure.

[0048] The present application can prepare a lithium iron phosphate positive electrode material with a surface mesoporous structure through the above-mentioned preparation method. The biological macromolecules with negative groups of yeast itself are used to adsorb the iron ions and ferrous ions in the iron source around the yeast, and then a phosphorus source is added and the pH is controlled to produce a porous intermediate precipitate. By controlling the culture environment of the yeast, the mesopore diameter on the surface of the lithium iron phosphate positive electrode material can be controlled between 40nm and 50nm. The lithium iron phosphate positive electrode material with this structure can increase the contact area of ​​the material, increase the lithium ion diffusion channel, and increase the lithium ion diffusion rate, which is beneficial to improve the lithium ion conductivity; and when the particles are deformed by stress, the mesopores give the particles a position for deformation, which reduces the generation of cracks in the particles, optimizes the cycle stability of the lithium iron phosphate positive electrode material, and increases the service life of the battery.

[0049] In one embodiment, in step S10, adding the carbon source and dry yeast into the solvent specifically includes: adding the carbon source into the solvent and stirring sufficiently so that the carbon source can be dissolved in the solvent; after the carbon source is sufficiently dissolved, adding the dry yeast into the solvent having the carbon source. The solvent may be water; dry yeast is also called yeast, which is a single-cell fungal microorganism.

[0050] It should be explained that yeast acts as a pore-forming agent in this application. Yeast contains a large number of negative macrogroups (electronegativity) on the outside, and the negative macrogroups on the yeast can adsorb cations, which is conducive to the formation of a large number of continuous mesopores in the obtained lithium iron phosphate positive electrode material. At the same time, the purpose of adding a carbon source to the yeast environment is to provide a nutritional environment for yeast cell breeding, and the carbon source can provide nutrients for the yeast; the carbon source can also be used as a coating material or mixed material for the lithium iron phosphate positive electrode material to provide conductive carbon for the synthesized lithium iron phosphate positive electrode material.

[0051] In one embodiment, in step S10, the dry yeast is cultured at a temperature ranging from 25°C to 30°C. The culture temperature of the dry yeast is within the above range to ensure the activity of the yeast and the number of yeast reproduction. When the culture temperature is too high or too low, the yeast reproduction rate will decrease, the yeast metabolic function will be disordered, the yeast will not be able to reproduce normally, and even the yeast will die, resulting in a small number of cultured yeast. Optionally, the dry yeast culture temperature can be 25°C, 26°C, 27°C, 28°C, 29°C, or 30°C.

[0052] In one embodiment, in step S10, the dry yeast culture time ranges from 0.1h to 1.5h. The culture time of the dry yeast is within the above range to ensure the number of yeasts. When the culture time is too short, the number of cultured yeasts is small; when the culture time is too long, the number of cultured yeasts is too large. Optionally, the culture temperature of the dry yeast can be 0.1h, 0.3h, 0.5h, 0.7h, 0.9h, 1.1h, 1.3h, 1.5h.

[0053] It is understandable that yeast is used as a pore-forming agent, and the amount of yeast is directly related to the number of mesopores produced and the size of the mesopores, that is, the porosity on the lithium iron phosphate cathode material. When the amount of yeast is too much, the number of mesopores will increase or the mesopores will be too large, and the porosity on the lithium iron phosphate cathode material will increase; when the amount of yeast is too little, the number of mesopores will decrease or the mesopores will be too small, and the porosity on the lithium iron phosphate cathode material will decrease. Therefore, the culture environment of the dry yeast (yeast) provided above is directly related to the porosity of the obtained lithium iron phosphate cathode material, that is, it is related to the performance of the lithium iron phosphate cathode material.

[0054] In one implementation, please refer to Figure 2In step S20, the dissolved iron source and the dissolved phosphorus source are sequentially mixed into the first solution, and a ferrophosphorus intermediate is obtained after drying, which specifically includes the following steps:

[0055] Step S21, mixing the dissolved iron source into the first solution, and obtaining a second solution after sufficient stirring.

[0056] Step S22, mixing the dissolved phosphorus source into the second solution, and obtaining a ferrophosphorus intermediate after drying.

[0057] In one embodiment, in step S21, the dissolved iron source is mixed into the first solution, specifically comprising: adding the iron source into a solvent and stirring sufficiently so that the iron source can be dissolved in the solvent; and then adding the solution containing the iron source into the first solution and stirring sufficiently to mix. The solvent may be water.

[0058] In one embodiment, in step S21, the stirring temperature range after the iron source is mixed into the first solution is 25°C to 40°C. The stirring temperature range is within the above range to protect the living environment of the yeast, because in this step, the yeast needs to be used to adsorb the cations in the iron source, so the activity of the yeast must be ensured. When the stirring temperature is too high or too low, the yeast will be inactivated and unable to adsorb cations. Optionally, the stirring temperature after the iron source is mixed into the first solution can be 25°C, 26°C, 28°C, 30°C, 32°C, 34°C, 36°C, 38°C, or 40°C.

[0059] In one embodiment, in step S21, the stirring time after the iron source is mixed into the first solution is in the range of 3h to 20h. The stirring time is within the above range in order to allow the yeast and the iron source to be fully adsorbed. When the stirring time is too short, insufficient cations adsorbed on the yeast will result; when the stirring time is too long, waste will result, and the yeast may continue to reproduce. Optionally, the stirring time after the iron source is mixed into the first solution can be 3h, 4h, 6h, 8h, 10h, 12h, 14h, 16h, 18h, 20h.

[0060] In one embodiment, in step S22, the dissolved phosphorus source is mixed into the second solution, specifically comprising: adding the phosphorus source into a solvent and stirring sufficiently so that the phosphorus source can be dissolved in the solvent; and then adding the solution containing the phosphorus source into the second solution and stirring sufficiently to mix. The solvent may be water.

[0061] In one embodiment, in step S22, the ferrophosphorus intermediate is obtained after drying, which specifically includes: the stirred solution is allowed to stand, and the ferrophosphorus intermediate is obtained after suction filtration and multiple washings. The washing liquid may be water, and the number of washings may be three or more.

[0062] In one embodiment, in step S22, the stirring pH value after the phosphorus source is mixed into the second solution is in the range of 4.5 to 7. The stirring pH value within the above range is conducive to the formation of a porous (ferric phosphate or ferrous phosphate) ferrophosphorus intermediate precipitate. When the stirring pH value is too low or too high, it will affect the formation of the precipitate. Optionally, the stirring pH value after the phosphorus source is mixed into the second solution can be 4.5, 5, 5.5, 6, 6.5, 7.

[0063] In one embodiment, in step S22, the stirring time after the phosphorus source is mixed into the second solution is in the range of 0.5h to 3h. The stirring time is within the above range in order to allow the iron source and the phosphorus source to fully react. When the stirring time is too short, insufficient precipitation of the phosphorus-iron intermediate will result; when the stirring time is too long, waste will result. Optionally, the stirring time after the phosphorus source is mixed into the second solution can be 0.5h, 1h, 1.5h, 2h, 2.5h, 3h.

[0064] In one embodiment, in step S22, the time range of standing still after stirring is 5 hours to 24 hours. Optionally, the time of standing still after stirring can be 5 hours, 6 hours, 8 hours, 10 hours, 12 hours, 14 hours, 16 hours, 18 hours, 20 hours, 22 hours, or 24 hours.

[0065] It should be noted that in the present application, the iron source and the phosphorus source need to be added to the solution containing yeast in steps, because the pore-forming method provided in the present application is different from other methods in the prior art. The iron source is first added in order to utilize the large negative groups outside the yeast to adsorb the iron source cations, and adsorb the iron ions and ferrous ions in the iron source around the yeast, thereby facilitating the formation of subsequent mesopores. After the cations are adsorbed outside the yeast, a phosphorus source is added and the pH value is controlled, the phosphorus source reacts with the iron ions and forms a phosphorus-iron intermediate precipitate, and mesopores are formed in the phosphorus-iron intermediate.

[0066] In one embodiment, in step S30, the ferrophosphorus intermediate and the lithium source are fully mixed to obtain a precursor, which specifically includes: fully ball-milling the ferrophosphorus intermediate and the lithium source, and rolling the obtained solid after mixing to obtain the precursor.

[0067] In one embodiment, when the lithium iron phosphate positive electrode material is doped with other metals, in step S30, the ferrophosphorus intermediate is fully mixed with the lithium source to obtain a precursor, specifically including: fully ball-milling the ferrophosphorus intermediate with the lithium source and the doped metal source, and rolling the obtained solid after mixing to obtain a precursor.

[0068] In this application, the obtained precursor needs to be rolled because the biomacromolecule synthesis using yeast cells will result in more mesopores in the ferrophosphorus intermediate, which is not conducive to the specific surface area and bulk density of the final product. After simple rolling, the mesopores or gaps in the ferrophosphorus intermediate can be appropriately reduced, which is more conducive to the combination of some mesopores during the sintering process, controlling the size of the mesopores of the final product, forming a lithium iron phosphate positive electrode material with mesopores, and appropriately increasing the bulk density of the powder (including loose density and compacted density).

[0069] In one implementation, please refer to Figure 3 In step S40, the precursor is sintered and then crushed, which specifically includes the following steps:

[0070] Step S41, placing the precursor in an inert atmosphere for a first stage of sintering, and crushing the solid obtained after the first stage of sintering to obtain a sintered product.

[0071] Step S42, placing the first sintered product in an inert atmosphere for a second sintering, and crushing the obtained solid after the second sintering to obtain a lithium iron phosphate positive electrode material with a surface mesoporous structure.

[0072] In one embodiment, in step S41, the heating rate of the first sintering stage is in the range of 1°C / min to 10°C / min. Optionally, the heating rate of the first sintering stage may be 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, or 10°C / min.

[0073] In one embodiment, in step S41, the sintering temperature of the first stage sintering ranges from 150° C. to 360° C. Optionally, the sintering temperature of the first stage sintering may be 150° C., 160° C., 180° C., 200° C., 220° C., 240° C., 260° C., 280° C., 300° C., 320° C., 340° C., or 360° C.

[0074] In one embodiment, in step S41, the sintering time of the first stage sintering ranges from 1 hour to 10 hours. Optionally, the sintering time of the first stage sintering can be 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, or 10 hours.

[0075] It should be explained that the first stage of sintering in this application is pre-sintering, which is not only for nucleation of the material, but also for the formation of an ideal mesoporous structure. When the first stage sintering temperature is too high, the particles will be formed prematurely, which is not conducive to the formation of an ideal mesoporous structure; when the first stage sintering temperature is too low, the volatile matter will be too high and the particles will not be able to nucleate. And after sintering, when cooled to room temperature, the obtained solid is crushed using a wall breaker to obtain a sintered product.

[0076] In one embodiment, in step S42, the heating rate of the second sintering stage is in the range of 12°C / min to 20°C / min. Optionally, the heating rate of the second sintering stage can be 12°C / min, 13°C / min, 14°C / min, 15°C / min, 16°C / min, 17°C / min, 18°C / min, 19°C / min, or 20°C / min.

[0077] In one embodiment, in step S42, the sintering temperature of the second stage sintering ranges from 650° C. to 750° C. Optionally, the sintering temperature of the second stage sintering may be 650° C., 660° C., 670° C., 680° C., 690° C., 700° C., 710° C., 720° C., 730° C., 740° C., or 750° C.

[0078] In one embodiment, in step S42, the sintering time of the second stage sintering ranges from 5 hours to 15 hours. Optionally, the sintering time of the second stage sintering can be 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, or 15 hours.

[0079] In one embodiment, the ratio of the added mass of dry yeast to the molar amount of iron in the iron source is 1g to 10g: 1mol. The added mass of dry yeast that meets the above requirements can ensure the number and size of the mesopores created to avoid uneven distribution of mesopores or excessive or small porosity. Optionally, the ratio of the added mass of dry yeast to the molar amount of iron in the iron source can be 1g: 1mol, 2g: 1mol, 3g: 1mol, 4g: 1mol, 5g: 1mol, 6g: 1mol, 7g: 1mol, 8g: 1mol, 9g: 1mol, 10g: 1mol.

[0080] In one embodiment, the added mass of the carbon source is 3% to 10% of the theoretical output of the lithium iron phosphate positive electrode material. The mass proportion of the carbon source in the lithium iron phosphate positive electrode material meets the above range, so that the amount of carbon source used can not only provide nutrients for yeast, but also provide conductive carbon for the synthesis of lithium iron phosphate, thereby increasing the lithium ion transmission rate; at the same time, it will not cause excessive in-situ carbon coating, making it difficult for lithium ions to detach at the interface between the particles and the carbon layer, thereby reducing the electrochemical impedance (in a specific embodiment, the chemical impedance of the material is less than 50Ω), which is beneficial to the improvement of the electrochemical performance of the material. Optionally, the mass proportion of the carbon source in the lithium iron phosphate positive electrode material can be 3%, 4%, 5%, 6%, 7%, 8%, 9%, or 10%.

[0081] In one embodiment, the molar ratio of the iron source, the phosphorus source, and the lithium source is in the range of (0.93-0.99): (0.98-1.00): (1.01-1.08). Optionally, the molar ratio of the phosphorus source to the lithium source can be 0.93: (0.98-1.00): (1.01-1.08), 0.96: (0.98-1.00): (1.01-1.08), 0.99: (0.98-1.00): (1.01-1.08), (0.93-0.99): 0.98: (1.01-1.08), (0.9 3~0.99):0.99:(1.01~1.08), (0.93~0.99):1:(1.01~1.08), (0.93~0.99):(0.98~1.00):1.01, (0.93~0.99):(0.98~1.00):1.05, (0.93~0.99):(0.98~1.00):1.08.

[0082] In one embodiment, the groups carried by the dry yeast include one or more of carboxyl groups, phosphate groups, and sulfonic acid groups.

[0083] In one embodiment, the carbon source includes one or more of glucose, maltose, fructose, and sucrose.

[0084] In one embodiment, the iron source includes one or more of ferric nitrate, ferrous nitrate, ferric sulfate, ferrous sulfate, ferric chloride, ferrous chloride, ferrous acetate, and ferrous acetate.

[0085] In one embodiment, the phosphorus source includes one or more of phosphoric acid, ammonium hydrogen phosphate, diammonium hydrogen phosphate, sodium phosphate, and potassium phosphate.

[0086] In one embodiment, the lithium source includes one or more of lithium oxide, lithium hydroxide, lithium oxalate, lithium carbonate, lithium acetate, and lithium phosphate.

[0087] In one embodiment, the lithium iron phosphate positive electrode material further includes overdoped metal elements, and the doped metal elements include one or more of Mg, Al, Ti, V, Cr, Mn, Nb, and Mo. Specifically, the doped metal source containing the doped metal elements can be added simultaneously with the lithium source in step S30. In addition, after doping the lithium iron phosphate positive electrode material with metal elements, the lithium ion diffusion channel can be shortened, the lithium ion diffusion surface can be expanded, the diffusion rate of lithium ions can be increased, and the electrochemical polarization can be reduced.

[0088] In one embodiment, the amount of the doped metal element is 0.4% to 1.2% of the lithium or iron content of the theoretically synthesized lithium iron phosphate. Optionally, the amount of the doped metal element is 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2% of the lithium or iron content of the theoretically synthesized lithium iron phosphate.

[0089] In one embodiment, in step S22, the pH value may be adjusted using one or more of dilute hydrochloric acid, dilute sulfuric acid, dilute acetic acid, oxalic acid solution, and the like.

[0090] In one embodiment, in step S40, the sintering furnace used includes a high-temperature sintering furnace with a protective atmosphere, such as a tubular furnace, a roller kiln, or a rotary kiln. The inert atmosphere includes one or more of nitrogen and argon.

[0091] The present application also provides a lithium iron phosphate positive electrode material.

[0092] In one embodiment, the lithium iron phosphate positive electrode material has a surface mesoporous structure. Specifically, the surface of the lithium iron phosphate positive electrode material is formed with inwardly recessed mesopores. The lithium iron phosphate positive electrode material provided in the present application has good strain capacity during the cycle, because the mesoporous structure on the lithium iron phosphate positive electrode material can provide more contact sites for the material, so that the lithium ion diffusion coefficient can be correspondingly improved, and the particles greatly reduce deformation and cracking during the cycle, reducing lithium consumption, so it has excellent cycle performance. And the battery prepared by the positive electrode material has a first charge specific capacity of 160mAh / g to 166mAh / g at room temperature, and the 1C discharge capacity retention rate can reach more than 97%.

[0093] In one embodiment, the pores of the mesoporous structure are uniformly distributed and the pore size is between 40nm and 50nm. The pore size of the mesopores meets the above range, which can ensure the cycle performance of the lithium iron phosphate positive electrode material and its structural stability. Optionally, the pore size of the mesopores can be 40nm, 41nm, 42nm, 43nm, 44nm, 45nm, 46nm, 47nm, 48nm, 49nm, 50nm.

[0094] In one embodiment, the lithium ion transfer rate of the lithium iron phosphate positive electrode material is in the range of 1.06×10 -13 m 2 / s~1.00×10 -14 m 2 / s. Optionally, the lithium ion transfer rate of the lithium iron phosphate positive electrode material can be 1.06×10 -13 m 2 / s, 9.00×10 -14 m 2 / s, 8.00×10 -14 m 2 / s, 7.00×10 -14 m 2 / s, 6.00×10 -14 m 2 / s, 5.00×10 -14 m 2 / s, 4.00×10 -14 m 2 / s, 3.00×10 -14 m 2 / s, 2.00×10 -14 m 2 / s, 1.00×10 -14 m 2 / s.

[0095] In one embodiment, the electronic conductivity of the lithium iron phosphate positive electrode material is in the range of 1×10 -7 S / cm~1×10 - 8 S / cm. Optionally, the electronic conductivity of the lithium iron phosphate cathode material can be 1×10 -7 S / cm, 8×10 -8 S / cm, 6×10 - 8 S / cm, 4×10 -8 S / cm, 2×10 -8 S / cm, 1×10 -8 S / cm.

[0096] In one embodiment, the bulk density of the lithium iron phosphate cathode material can reach 0.5 g / cm 3 ~0.7g / cm 3 Optionally, the bulk density of the lithium iron phosphate cathode material can be 0.5 g / cm 3 , 0.6g / cm 3 , 0.7g / cm 3 .

[0097] In one embodiment, the compaction density of the lithium iron phosphate cathode material can reach 2.45 g / cm3 ~2.52g / cm 3 Optionally, the compaction density of the lithium iron phosphate cathode material can be 2.45 g / cm 3 , 2.46g / cm 3 , 2.47g / cm 3 , 2.48g / cm 3 , 2.49g / cm 3 , 2.5g / cm 3 , 2.51g / cm 3 , 2.52g / cm 3 .

[0098] The present application also provides a positive electrode plate.

[0099] In one embodiment, the positive electrode sheet includes a positive electrode current collector and a positive electrode film layer located on at least one surface of the positive electrode current collector, and the positive electrode film layer includes the lithium iron phosphate positive electrode material obtained by the above-mentioned preparation method or the above-mentioned lithium iron phosphate positive electrode material. Optionally, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is arranged on any one or both of the two opposite surfaces of the positive electrode current collector.

[0100] In one embodiment, the positive electrode film layer may further include a positive electrode conductive agent. The present application has no particular restrictions on the type of the positive electrode conductive agent. As an example, the positive electrode conductive agent includes at least one of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene oxide, and carbon nanofibers. In some embodiments, based on the total mass of the positive electrode film layer, the mass percentage of the positive electrode conductive agent is ≤5%.

[0101] In one embodiment, the positive electrode film layer may further optionally include a positive electrode binder. The present application has no particular restrictions on the type of positive electrode binder. As an example, the positive electrode binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylic resin. In some embodiments, based on the total mass of the positive electrode film layer, the mass percentage of the positive electrode binder is ≤5%.

[0102] In one embodiment, the positive electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, aluminum foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include at least one of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. As an example, the polymer material base layer may include at least one of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE).

[0103] In one embodiment, the positive electrode film layer is usually formed by coating the positive electrode slurry on the positive electrode current collector, drying, and cold pressing. The positive electrode slurry is usually formed by dispersing the positive electrode active material, optional conductive agent, optional binder, and any other components in a solvent and stirring them uniformly. The solvent can be N-methylpyrrolidone (NMP), but is not limited thereto.

[0104] The present application also provides a secondary battery.

[0105] In one embodiment, the secondary battery comprises the lithium iron phosphate cathode material obtained by the above preparation method or the above lithium iron phosphate cathode material. The secondary battery of the present application comprises the lithium iron phosphate cathode material of the embodiment of the present application or the lithium iron phosphate cathode material prepared by the method of the embodiment of the present application.

[0106] The technical solution of the present application is described in detail below through specific embodiments.

[0107] Example 1

[0108] A method for preparing a lithium iron phosphate positive electrode material comprises the following steps:

[0109] (1) Glucose was dissolved in water by stirring, and dry yeast was added and placed at 25° C. for 1 hour to obtain a mixed first solution.

[0110] (2) After ferrous sulfate is dissolved in water by stirring, the solution is poured into the first mixed solution, stirred, and placed at 25° C. for 8 hours to obtain a second mixed solution.

[0111] (3) After diammonium hydrogen phosphate is dissolved in water by stirring, it is poured into the mixed second solution, and the pH is adjusted to 5 with dilute hydrochloric acid, and stirred for 1 hour, and then allowed to stand for 5 hours. After suction filtration and water washing 3 times, a ferrophosphorus intermediate is obtained.

[0112] (4) The above-mentioned ferrophosphorus intermediate is transferred to a ball mill, mixed with lithium oxalate and manganese sulfate, and then simply rolled using a roller press to obtain a precursor.

[0113] (5) The prepared precursor was pre-sintered under an inert atmosphere at a heating rate of 10°C / min, a pre-sintering temperature of 230°C, and a pre-sintering time of 7.5 h. After cooling to room temperature, the obtained solid was crushed using a wall breaker to obtain a sintered product.

[0114] (6) The sintered product is placed in an inert atmosphere for sintering at a heating rate of 12°C / min, a sintering temperature of 750°C, and a sintering time of 10 hours. After cooling to room temperature, the product is pulverized by air flow to obtain a mesoporous lithium iron phosphate product.

[0115] Among them, in the above steps (1) to (6), iron nitrate: diammonium hydrogen phosphate: lithium oxalate are weighed according to the element ratio of Fe:P:Li=0.97:1.00:1.02, glucose is weighed according to 8% of the theoretical total amount of lithium iron phosphate, dry yeast: lithium iron phosphate is weighed according to the theoretical total amount of 1g:1mol, and manganese sulfate is weighed according to the Mn element being 0.6% of the Fe element.

[0116] The surface of the prepared lithium iron phosphate cathode material has a mesoporous structure with uniformly distributed pores and pore sizes between 40nm and 50nm. The surface morphology of the lithium iron phosphate cathode material can be referred to Figure 4 .

[0117] Example 2

[0118] A method for preparing a lithium iron phosphate positive electrode material comprises the following steps:

[0119] (1) Sucrose was stirred and dissolved in water, and dry yeast was added and placed at 30° C. for 1.5 h to obtain a mixed first solution.

[0120] (2) After ferric nitrate is dissolved in water by stirring, the solution is poured into the first mixed solution, stirred, and placed at 40° C. for 10 hours to obtain a second mixed solution.

[0121] (3) After sodium phosphate is dissolved in water by stirring, it is poured into the mixed second solution, and the pH is adjusted to 7 with acetic acid, and stirred for 2 hours. Then, it is allowed to stand for 18 hours. After suction filtration and washing with water three times, a ferrophosphorus intermediate is obtained.

[0122] (4) The above-mentioned ferrophosphorus intermediate is transferred to a ball mill, mixed with lithium carbonate and vanadium carbonate, and then simply rolled using a roller press to obtain a precursor.

[0123] (5) The prepared precursor was pre-sintered under an inert atmosphere at a heating rate of 2°C / min, a pre-sintering temperature of 350°C, and a pre-sintering time of 3 h. After cooling to room temperature, the obtained solid was crushed using a wall breaker to obtain a sintered product.

[0124] (6) The sintered product is placed in an inert atmosphere for sintering at a heating rate of 20°C / min, a sintering temperature of 700°C, and a sintering time of 13h. After cooling to room temperature, the product is pulverized by air flow to obtain a mesoporous lithium iron phosphate product.

[0125] In the above steps (1) to (6), the iron nitrate: sodium phosphate: lithium carbonate are weighed according to the element ratio of Fe:P:Li=0.97:1.00:1.02, sucrose is weighed according to 10% of the theoretical total amount of lithium iron phosphate, the theoretical total amount of dry yeast: lithium iron phosphate is weighed according to 2g:1mol, and vanadium carbonate is weighed according to the V element being 0.4% of the Li element.

[0126] The surface of the prepared lithium iron phosphate positive electrode material has a mesoporous structure with uniformly distributed pores and pore sizes between 40nm and 50nm.

[0127] Example 3

[0128] A method for preparing a lithium iron phosphate positive electrode material comprises the following steps:

[0129] (1) Fructose was stirred and dissolved in water, and dry yeast was added and placed at 30° C. for 0.1 h to obtain a mixed first solution.

[0130] (2) After ferric acetate is dissolved in water by stirring, the solution is poured into the first mixed solution, stirred, and placed at 35° C. for 20 hours to obtain a second mixed solution.

[0131] (3) After phosphoric acid is dissolved in water by stirring, it is poured into the mixed second solution, and the pH is adjusted to 4.5 with acetic acid, and stirred for 0.5 h. Then, it is allowed to stand for 5 h. After suction filtration and washing with water three times, a ferrophosphorus intermediate is obtained.

[0132] (4) The ferrophosphorus intermediate is transferred to a ball mill, mixed with lithium oxide, lithium hydroxide, titanium nitrate and magnesium nitrate, and then simply rolled using a roller press to obtain a precursor.

[0133] (5) Under an inert atmosphere, the prepared precursor was pre-sintered at a heating rate of 10°C / min, a pre-sintering temperature of 150°C, and a pre-sintering time of 5 h. After cooling to room temperature, the obtained solid was crushed using a wall breaker to obtain a sintered product.

[0134] (6) The sintered product is placed in an inert atmosphere for sintering at a heating rate of 12°C / min, a sintering temperature of 650°C, and a sintering time of 5h. After cooling to room temperature, the product is pulverized by air flow to obtain a mesoporous lithium iron phosphate product.

[0135] Among them, in the above steps (1) to (6), the element ratio of iron acetate: phosphoric acid: lithium oxide and lithium hydroxide is Fe: P: Li = 0.95: 0.98: 1.08, the Li element ratio of lithium oxide and lithium hydroxide is 2: 3, fructose is 3% of the theoretical total amount of lithium iron phosphate, the theoretical total amount of dry yeast: lithium iron phosphate is 5g: 1mol, and titanium nitrate and magnesium nitrate are weighed according to the ratio of Ti and Mg elements to Fe element of 0.65%.

[0136] The surface of the prepared lithium iron phosphate positive electrode material has a mesoporous structure with uniformly distributed pores and pore sizes between 40nm and 50nm.

[0137] Example 4

[0138] A method for preparing a lithium iron phosphate positive electrode material comprises the following steps:

[0139] (1) The mixed carbon source was stirred and dissolved in water, and dry yeast was added and placed at 27° C. for 1 hour to obtain a mixed first solution.

[0140] (2) After ferric chloride is dissolved in water by stirring, the solution is poured into the first mixed solution, stirred, and placed at 33° C. for 7 hours to obtain a second mixed solution.

[0141] (3) After diammonium hydrogen phosphate is stirred and dissolved in water, it is poured into the mixed second solution, and the pH is adjusted to 5 using dilute sulfuric acid, and stirred for 3 hours. Then, it is allowed to stand for 24 hours. After suction filtration and water washing 3 times, a ferrophosphorus intermediate is obtained.

[0142] (4) The ferrophosphorus intermediate is transferred to a ball mill, mixed with lithium oxalate, vanadium pentoxide and niobium nitrate, and then simply rolled using a roller press to obtain a precursor.

[0143] (5) Under an inert atmosphere, the prepared precursor was pre-sintered at a heating rate of 1°C / min, a pre-sintering temperature of 360°C, and a pre-sintering time of 1 h. After cooling to room temperature, the obtained solid was crushed using a wall breaker to obtain a sintered product.

[0144] (6) The sintered product is placed in an inert atmosphere for sintering at a heating rate of 18°C / min, a sintering temperature of 680°C, and a sintering time of 15h. After cooling to room temperature, the product is pulverized by air flow to obtain a mesoporous lithium iron phosphate product.

[0145] Among them, in the above steps (1) to (6), ferric chloride: diammonium hydrogen phosphate: lithium oxalate are in an element ratio of Fe: P: Li = 0.93: 0.99: 1.05, the mixed carbon source is maltose and sucrose in a ratio of 2: 3, the mixture is in a theoretical total amount of 6% of lithium iron phosphate, the theoretical total amount of dry yeast: lithium iron phosphate is 4g: 1mol, and vanadium pentoxide and niobium nitrate are weighed in a ratio of V and Nb elements to 1.2% of Fe element.

[0146] The surface of the prepared lithium iron phosphate positive electrode material has a mesoporous structure with uniformly distributed pores and pore sizes between 40nm and 50nm.

[0147] Example 5

[0148] A method for preparing a lithium iron phosphate positive electrode material comprises the following steps:

[0149] (1) Glucose was dissolved in water by stirring, and dry yeast was added and placed at 25° C. for 1 hour to obtain a mixed first solution.

[0150] (2) After ferrous sulfate is dissolved in water by stirring, the solution is poured into the first mixed solution, stirred, and placed at 25° C. for 8 hours to obtain a second mixed solution.

[0151] (3) After diammonium hydrogen phosphate is dissolved in water by stirring, it is poured into the mixed second solution, and the pH is adjusted to 5 with dilute hydrochloric acid, and stirred for 1 hour, and then allowed to stand for 5 hours. After suction filtration and water washing 3 times, a ferrophosphorus intermediate is obtained.

[0152] (4) The above-mentioned ferrophosphorus intermediate is transferred to a ball mill, mixed with lithium oxalate, and then simply rolled using a roller press to obtain a precursor.

[0153] (5) The prepared precursor was pre-sintered under an inert atmosphere at a heating rate of 10°C / min, a pre-sintering temperature of 230°C, and a pre-sintering time of 7.5 h. After cooling to room temperature, the obtained solid was crushed using a wall breaker to obtain a sintered product.

[0154] (6) The sintered product is placed in an inert atmosphere for sintering at a heating rate of 12°C / min, a sintering temperature of 750°C, and a sintering time of 10 hours. After cooling to room temperature, the product is pulverized by air flow to obtain a mesoporous lithium iron phosphate product.

[0155] Among them, in the above steps (1) to (6), iron nitrate: diammonium hydrogen phosphate: lithium oxalate are weighed according to the element ratio of Fe:P:Li=0.97:1.00:1.02, glucose is weighed according to 8% of the theoretical total amount of lithium iron phosphate, and dry yeast: lithium iron phosphate is weighed according to the theoretical total amount of 1g:1mol.

[0156] The surface of the prepared lithium iron phosphate positive electrode material has a mesoporous structure with uniformly distributed pores and pore sizes between 40nm and 50nm.

[0157] Comparative Example 1

[0158] A method for preparing a lithium iron phosphate positive electrode material comprises the following steps:

[0159] (1) Dissolve glucose in water with stirring to obtain a first solution.

[0160] (2) After ferrous sulfate is dissolved in water by stirring, the solution is poured into the first solution, stirred, and placed at 25° C. for 8 hours to obtain a mixed second solution.

[0161] (3) After diammonium hydrogen phosphate is dissolved in water by stirring, it is poured into the mixed second solution, and the pH is adjusted to 5 with dilute hydrochloric acid, and stirred for 1 hour, and then allowed to stand for 5 hours. After suction filtration and water washing 3 times, a ferrophosphorus intermediate is obtained.

[0162] (4) The above-mentioned ferrophosphorus intermediate is transferred to a ball mill, mixed with lithium oxalate and manganese sulfate, and then simply rolled using a roller press to obtain a precursor.

[0163] (5) The prepared precursor was pre-sintered under an inert atmosphere at a heating rate of 10°C / min, a pre-sintering temperature of 230°C, and a pre-sintering time of 7.5 h. After cooling to room temperature, the obtained solid was crushed using a wall breaker to obtain a sintered product.

[0164] (6) The sintered product is placed in an inert atmosphere for sintering at a heating rate of 12°C / min, a sintering temperature of 750°C, and a sintering time of 10 hours. After cooling to room temperature, the product is pulverized by air flow to obtain a mesoporous lithium iron phosphate product.

[0165] Among them, in the above steps (1) to (6), iron nitrate: diammonium hydrogen phosphate: lithium oxalate are weighed according to the element ratio of Fe:P:Li=0.97:1.00:1.02, glucose is weighed according to 8% of the theoretical total amount of lithium iron phosphate, and manganese sulfate is weighed according to the Mn element being 0.6% of the Fe element.

[0166] The surface of the lithium iron phosphate positive electrode material obtained in this comparative example 1 has no distributed holes. The surface morphology of the lithium iron phosphate positive electrode material can be referred to Figure 5 .

[0167] Comparative Example 2

[0168] A method for preparing a lithium iron phosphate positive electrode material comprises the following steps:

[0169] (1) Glucose was dissolved in water by stirring, and dry yeast was added and placed at 25° C. for 2.5 hours to obtain a mixed first solution.

[0170] (2) After ferrous sulfate is dissolved in water by stirring, the solution is poured into the first mixed solution, stirred, and placed at 25° C. for 10 hours to obtain a second mixed solution.

[0171] (3) After diammonium hydrogen phosphate is dissolved in water by stirring, it is poured into the mixed second solution, and the pH is adjusted to 5 with dilute hydrochloric acid, and stirred for 1 hour, and then allowed to stand for 5 hours. After suction filtration and water washing 3 times, a ferrophosphorus intermediate is obtained.

[0172] (4) The above-mentioned ferrophosphorus intermediate is transferred to a ball mill, mixed with lithium oxalate, and then simply rolled using a roller press to obtain a precursor.

[0173] (5) The prepared precursor was pre-sintered under an inert atmosphere at a heating rate of 10°C / min, a pre-sintering temperature of 230°C, and a pre-sintering time of 7.5 h. After cooling to room temperature, the obtained solid was crushed using a wall breaker to obtain a sintered product.

[0174] (6) The sintered product is placed in an inert atmosphere for sintering at a heating rate of 12°C / min, a sintering temperature of 750°C, and a sintering time of 10 hours. After cooling to room temperature, the product is pulverized by air flow to obtain a mesoporous lithium iron phosphate product.

[0175] Among them, in the above steps (1) to (6), iron nitrate: diammonium hydrogen phosphate: lithium oxalate are weighed according to the element ratio of Fe:P:Li=0.97:1.00:1.02, glucose is weighed according to 8% of the theoretical total amount of lithium iron phosphate, and dry yeast: lithium iron phosphate is weighed according to the theoretical total amount of 5g:1mol.

[0176] The surface of the lithium iron phosphate positive electrode material obtained in this comparative example 2 has holes with a pore size greater than 50 nm.

[0177] Comparative Example 3

[0178] A method for preparing a lithium iron phosphate positive electrode material comprises the following steps:

[0179] (1) Glucose was dissolved in water by stirring, and dry yeast was added and placed at 20° C. for 0.5 h to obtain a mixed first solution.

[0180] (2) After ferrous sulfate is dissolved in water by stirring, the solution is poured into the first mixed solution, stirred, and placed at 25° C. for 8 hours to obtain a second mixed solution.

[0181] (3) After diammonium hydrogen phosphate is dissolved in water by stirring, it is poured into the mixed second solution, and the pH is adjusted to 5 with dilute hydrochloric acid, and stirred for 1 hour, and then allowed to stand for 5 hours. After suction filtration and water washing 3 times, a ferrophosphorus intermediate is obtained.

[0182] (4) The above-mentioned ferrophosphorus intermediate is transferred to a ball mill, mixed with lithium oxalate, and then simply rolled using a roller press to obtain a precursor.

[0183] (5) The prepared precursor was pre-sintered under an inert atmosphere at a heating rate of 10°C / min, a pre-sintering temperature of 230°C, and a pre-sintering time of 7.5 h. After cooling to room temperature, the obtained solid was crushed using a wall breaker to obtain a sintered product.

[0184] (6) The sintered product is placed in an inert atmosphere for sintering at a heating rate of 12°C / min, a sintering temperature of 750°C, and a sintering time of 10 hours. After cooling to room temperature, the product is pulverized by air flow to obtain a mesoporous lithium iron phosphate product.

[0185] Among them, in the above steps (1) to (6), iron nitrate: diammonium hydrogen phosphate: lithium oxalate are weighed according to the element ratio of Fe:P:Li=0.97:1.00:1.02, glucose is weighed according to 8% of the theoretical total amount of lithium iron phosphate, and dry yeast: lithium iron phosphate is weighed according to the theoretical total amount of 0.5g:1mol.

[0186] The surface of the lithium iron phosphate positive electrode material obtained in this comparative example 3 has holes with a pore size of less than 40 nm distributed thereon.

[0187] Comparative Example 4

[0188] A method for preparing a lithium iron phosphate positive electrode material comprises the following steps:

[0189] (1) Glucose was dissolved in water by stirring, and dry yeast was added and placed at 45° C. for 1.5 h to obtain a mixed first solution.

[0190] (2) After ferrous sulfate is dissolved in water by stirring, the solution is poured into the first mixed solution, stirred, and placed at 25° C. for 8 hours to obtain a second mixed solution.

[0191] (3) After diammonium hydrogen phosphate is dissolved in water by stirring, it is poured into the mixed second solution, and the pH is adjusted to 5 with dilute hydrochloric acid, and stirred for 1 hour, and then allowed to stand for 5 hours. After suction filtration and water washing 3 times, a ferrophosphorus intermediate is obtained.

[0192] (4) The above-mentioned ferrophosphorus intermediate is transferred to a ball mill, mixed with lithium oxalate, and then simply rolled using a roller press to obtain a precursor.

[0193] (5) The prepared precursor was pre-sintered under an inert atmosphere at a heating rate of 10°C / min, a pre-sintering temperature of 230°C, and a pre-sintering time of 7.5 h. After cooling to room temperature, the obtained solid was crushed using a wall breaker to obtain a sintered product.

[0194] (6) The sintered product is placed in an inert atmosphere for sintering at a heating rate of 12°C / min, a sintering temperature of 750°C, and a sintering time of 10 hours. After cooling to room temperature, the product is pulverized by air flow to obtain a mesoporous lithium iron phosphate product.

[0195] Among them, in the above steps (1) to (6), iron nitrate: diammonium hydrogen phosphate: lithium oxalate are weighed according to the element ratio of Fe:P:Li=0.97:1.00:1.02, glucose is weighed according to 8% of the theoretical total amount of lithium iron phosphate, and dry yeast: lithium iron phosphate is weighed according to the theoretical total amount of 1g:1mol.

[0196] The surface of the lithium iron phosphate positive electrode material obtained in Comparative Example 4 has pores with a pore size between 10 nm and 100 nm.

[0197] Test Case

[0198] Battery preparation:

[0199] The lithium iron phosphate positive electrode materials provided in the above-mentioned Examples 1 to 5 and Comparative Examples 1 to 4 are prepared as positive electrode sheets. The preparation method of the positive electrode sheet includes: mixing the lithium iron phosphate positive electrode material, polyvinylidene fluoride and carbon black in a ratio of 96.5%, 2.2% and 1.3% by mass, respectively, and mixing and fully stirring with a certain amount of N-methylpyrrolidone to obtain a positive electrode slurry, drying the positive electrode slurry on the surface of the positive electrode current collector at a temperature of 120° C. on a coating machine to form a film, and then rolling on a roller press to obtain a positive electrode sheet.

[0200] The positive electrode sheets provided in the above-mentioned Examples 1 to 5 and Comparative Examples 1 to 4 are prepared as secondary batteries. The preparation method of the secondary battery includes: using graphite as the negative electrode sheet, coating, slicing, rolling, slitting, welding, and winding the positive electrode sheet, the separator, and the negative electrode sheet to obtain a rolled battery cell, drying at 80°C for 48 hours, and then taking the electrolyte to fill the battery and seal it, and after 24 hours of formation, capacity division, and aging, a secondary battery is prepared. The selection of the electrolyte can be based on any electrolyte suitable for lithium-ion batteries in this industry, and the type of the electrolyte is not limited here.

[0201] The secondary batteries provided in the above-mentioned Examples 1 to 5 and Comparative Examples 1 to 4 were subjected to electrochemical performance tests, and the test conditions were as follows:

[0202] Conventional charge and discharge test:

[0203] The electrochemical performance was tested on the Xinwei battery testing system at room temperature of 25°C, and 1C constant current was used for charge and discharge tests.

[0204] Cycle performance test:

[0205] The secondary battery was tested for charge and discharge cycles using a 1C constant current, with a charge and discharge voltage range of 2.5V to 3.65V, and repeated charge and discharge cycles. Normal temperature cycles were performed in a 25°C constant temperature box, and high temperature cycles were performed in a 45°C constant temperature box. The capacity retention rate of the secondary battery at different cycle numbers was calculated. Among them, the capacity retention rate (%) of the battery after N cycles = (discharge capacity of the Nth cycle / first discharge capacity) × 100%, where N is the number of cycles of the battery.

[0206] Impedance test:

[0207] Place the cleaned electrodes in the corresponding positions of the electrochemical workstation and ensure that the electrodes are properly wired. Start the electrochemical workstation, select the impedance measurement mode, and set the test frequency to: 0.01-10 5 Hz. After the system is stable, start recording the impedance data of the electrode.

[0208] The secondary battery results are shown in Table 1 below:

[0209] Table 1. Test results of secondary batteries assembled in Examples and Comparative Examples

[0210]

[0211]

[0212] From the test results of Example 1 and Comparative Example 1 in Table 1, it can be seen that the charge and discharge capacity of the secondary battery assembled with the lithium iron phosphate positive electrode material obtained in Example 1, as well as the capacity retention rate after 300 cycles are greater than those of the secondary battery in Comparative Example 1. This is due to the fact that the lithium iron phosphate positive electrode material in Example 1 has a surface mesoporous structure. The lithium iron phosphate positive electrode material prepared by the preparation method provided in this application has a mesoporous structure, the mesopores on the surface of the material are uniform, and the mesopore diameter is approximately distributed between 40 and 50 nm. The lithium iron phosphate material with this mesoporous structure reduces particle deformation and cracking during the cycle process, reduces lithium consumption, and is beneficial to the improvement of battery cycle performance. The lithium iron phosphate material can increase the contact surface between the material and the electrolyte, improve the capacity; improve the lithium ion diffusion rate, which is beneficial to improve the lithium ion conductivity, higher discharge capacity, and better capacity retention rate. At the same time, it can be seen from Table 1 that after the lithium iron phosphate positive electrode material prepared by the preparation method provided in this application is assembled into a 18650 full battery, at 25°C, the 1C discharge specific capacity reaches 136mAh / g, and it has good cycle performance and a lower attenuation rate.

[0213] From the test results of Example 1-Example 4 and Comparative Example 2-Comparative Example 4 in Table 1, it can be seen that the amount of yeast, the culture temperature, and the culture time will also have an impact on the lithium iron phosphate material with mesopores finally prepared. Any change in any condition will cause the charge and discharge capacity of the lithium iron phosphate material with mesopores to decrease or the capacity retention rate to decrease. For Comparative Example 2, the difference between Comparative Example 2 and Example 1 is that the yeast culture time in step (1) is longer, the stirring time in step (2) is longer, and the amount of dry yeast is larger, which leads to an increase in the pore size on the lithium iron phosphate positive electrode material. For Comparative Example 3, the difference between Comparative Example 3 and Example 1 is that the yeast culture temperature in step (1) is lower, the culture time is shorter, and the amount of dry yeast is less, which leads to a decrease in the pore size on the lithium iron phosphate positive electrode material. For Comparative Example 4, the difference between Comparative Example 4 and Example 1 is that the yeast culture temperature in step (1) is higher and the culture time is slightly longer, which leads to a wider distribution range of mesopores. However, compared with Comparative Example 1, the electrical performance of the above embodiments and comparative examples are significantly improved, which also illustrates that the solution provided in the present application can achieve the purpose of improving battery performance.

[0214] From the test results of Example 1 and Example 5 in Table 1, it can be seen that the solution provided by the present application can be applied to both doped lithium iron phosphate positive electrode materials and ordinary undoped lithium iron phosphate positive electrode materials. In addition, the charge and discharge capacity of the final material in Example 5 is lower than 130 mAh / g (less than Comparative Example 1) because doping can improve material performance, not caused by yeast pore formation.

[0215] In addition, in the embodiments and comparative examples of the present application, due to the relatively high carbon content, the carbon coating layer is thicker and more tightly coated, and the initial capacity of the positive electrode material is not fully released. During the cycle, the capacity is slowly released, resulting in a slight climb. After 300 cycles, the capacity retention rate may exceed 100%.

[0216] In the description of the embodiments of the present application, it should be noted that the orientation or positional relationship of terms such as "center", "up", "down", "left", "right", "vertical", "horizontal", "inside" and "outside" are based on the orientation or positional relationship described in the accompanying drawings, and are only for the convenience of describing the present application and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present application.

[0217] What is disclosed above is only a preferred embodiment of the present application, and it certainly cannot be used to limit the scope of rights of the present application. Ordinary technicians in this field can understand that all or part of the processes of implementing the above embodiment and equivalent changes made according to the claims of the present application are still within the scope covered by the present application.

Claims

1. A method for preparing a lithium iron phosphate positive electrode material, characterized in that: The preparation method comprises: adding a carbon source and dry yeast into a solvent, and culturing the dry yeast to obtain a first solution; The dissolved iron source and the dissolved phosphorus source are sequentially mixed into the first solution, and after drying, a phosphorus iron intermediate is obtained; The ferrophosphorus intermediate is fully mixed with a lithium source to obtain a precursor; The precursor is sintered and then crushed to obtain a lithium iron phosphate positive electrode material with a surface mesoporous structure.

2. The preparation method according to claim 1, characterized in that: The step of sequentially mixing the dissolved iron source and the dissolved phosphorus source into the first solution and drying to obtain a ferrophosphorus intermediate comprises: Mixing the dissolved iron source into the first solution, and obtaining a second solution after sufficient stirring; The dissolved phosphorus source is mixed into the second solution, and the ferrophosphorus intermediate is obtained after drying.

3. The preparation method according to claim 2, characterized in that: The stirring temperature range after the iron source is mixed into the first solution is 25° C. to 40° C., and the stirring time range is 3 h to 20 h; and / or The pH value of the solution after the phosphorus source is mixed into the second solution is in the range of 4.5 to 7 during stirring, the stirring time is in the range of 0.5 h to 3 h, and the standing time after stirring is in the range of 5 h to 24 h.

4. The preparation method according to claim 1, characterized in that: The ferrophosphorus intermediate is fully mixed with a lithium source to obtain a precursor, comprising: The ferrophosphorus intermediate and the lithium source are fully ball-milled and mixed, and the obtained solid is roll-pressed after mixing to obtain the precursor; or The ferrophosphorus intermediate is fully ball-milled with a lithium source and a doping metal source, and the obtained solid is roll-pressed after mixing to obtain the precursor.

5. The preparation method according to claim 1, characterized in that: The precursor is sintered and then crushed, comprising: Placing the precursor in an inert atmosphere for a first sintering, and crushing the solid obtained after the first sintering to obtain a sintered product; The first sintered product is placed in an inert atmosphere for a second sintering, and the solid obtained after the second sintering is crushed to obtain the lithium iron phosphate positive electrode material with a surface mesoporous structure.

6. The preparation method according to claim 5, characterized in that: The heating rate of the first sintering stage is in the range of 1°C / min to 10°C / min, the sintering temperature of the first sintering stage is in the range of 150°C to 360°C, and the sintering time of the first sintering stage is in the range of 1h to 10h; and / or The heating rate range of the second stage sintering is 12° C. / min to 20° C. / min, the sintering temperature range of the second stage sintering is 650° C. to 750° C., and the sintering time range of the second stage sintering is 5 h to 15 h.

7. The preparation method according to any one of claims 1 to 6, characterized in that: The dry yeast culture temperature ranges from 25°C to 30°C, and the dry yeast culture time ranges from 0.1h to 1.5h; and / or The ratio of the added mass of the dry yeast to the molar amount of the iron element in the iron source is 1 g to 10 g: 1 mol; and / or The added mass of the carbon source is 3% to 10% of the theoretical output of the lithium iron phosphate positive electrode material; and / or The molar ratio of the iron source, the phosphorus source, and the lithium source is in the range of (0.93-0.99): (0.98-1.00): (1.01-1.08); and / or The groups carried by the dry yeast include one or more of carboxyl, phosphate and sulfonic acid groups; and / or The carbon source includes one or more of glucose, maltose, fructose and sucrose.

8. A lithium iron phosphate positive electrode material, characterized in that: The surface of the lithium iron phosphate positive electrode material has a mesoporous structure, the holes of the mesoporous structure are evenly distributed and the pore size is between 40nm and 50nm; and / or The lithium ion transfer rate of the lithium iron phosphate positive electrode material is in the range of 1.06×10 -13 m 2 / s~1.00×10 -14 m 2 / s; and / or The electronic conductivity of the lithium iron phosphate positive electrode material is in the range of 1×10 -7 S / cm~1×10 -8 S / cm.

9. A positive electrode sheet, characterized in that: The positive electrode plate includes a positive electrode collector and a positive electrode film layer located on at least one surface of the positive electrode collector, and the positive electrode film layer includes the lithium iron phosphate positive electrode material obtained by the preparation method described in any one of claims 1 to 7 or the lithium iron phosphate positive electrode material described in claim 8.

10. A secondary battery, characterized in that: The invention comprises the lithium iron phosphate positive electrode material obtained by the preparation method according to any one of claims 1 to 7 or the lithium iron phosphate positive electrode material according to claim 8.